The role of Sharia compliance in achieving quality financial performance: An applied Research (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to find the relationship between Sharia compliance and the quality of financial performance. The research relied on the descriptive and quantitative approaches, where statistical methods were employed to analyze Sharia compliance and financial data for the financial performance variable. The study community included a group of Iraqi banks that were not sanctioned at the time, and a sample of seven banks listed on the Iraq Stock Exchange for the period (2020-2023) and one government bank was selected. The results showed that Sharia compliance plays a crucial role in achieving the quality of financial performance (as it prepares the compliance monitor report to include the calculated financial indicators (capital adequacy ratios, liquidity, profitability) and other ratios and ensures the bank's commitment to the standard ratios determined by the Central Bank of IraqBased on the results, the research recommends that the banks surveyed should focus on finding a kind of balance between liquidity and profitability and not leaving uninvested funds idle and working to benefit from them by investing them to obtain profits and thus raise the profitability ratios of banks.